The Effect of Students Knowledge about Environmental Pollution (High Knowledge Vs Low Knowledge) to Critical Thinking - Izzaty, Atiya Mustawli (Biosfer: Jurnal Pendidikan Biologi, 2014)
Environmental pollution has become a serious problem compromising human health. It is believed that providing knowledge about this matter, particularly for high school students, will improve their critical thinking by which participation to solve the problem increases. The purpose of this study was to determine the effect of students knowledge about environmental contamination to students critical thinking. This study was conducted in SMAN 54 Jakarta on May 2012 using ex post facto study method with post-test only control group design. Samples were taken from grade 10 students selected by simple random sampling. The result of prerequisite tests performed by t-test and the Kolmogorov-Smirnov test showed that data were homogenous and normally distributed while hypothesis testing by t-test at Î± = 0.001 it was found that students knowledge about environmental pollution has an effect to students critical thinking.